Analisis Daya Saing Pada Perusahaan Waste Water Treatment Menggunakan Bakteri X Dalam Mendukung Keberlanjutan Bisnis Agroindustri - Ainii, Aufaa Afiffah; Asnawi, Yudha Heryawan; Taryana, Asep (JURNAL AGROINDUSTRI HALAL, 2026)
The need for agro-industrial wastewater management has become a business opportunity for management services. However, this business requires sustainable competitiveness to survive. PT XYZ is a wastewater management service company for the agro-industry with a fluctuating margin value. The objective of this study is to analyze the company's competitiveness based on its resources.This research uses a mixed-method approach, combining expert interviews and performance assessment of each indicator with the VRIO approach, as well as quantitative descriptive analysis using mean values and weights. The results of the identification and analysis indicate that the main resources owned by the company are intangible resources and core competencies, while two other resources require improvement in the aspects of difficult to imitate and being well-organized. The findings of this study recommend improvements through innovation in the technical, documentation, and marketing aspects so that the company can achieve sustainable competitiveness. Furthermore, the company also needs to invest in tangible resources with innovation for long-term competitiveness and enhance the performance of its existing resources.